Isak 335 Training At Penuh Penghapan And Pelita Harapan Orphanages - Purba, Sahala; Wudjud, Wie Shi; Sitohang, Santy Aji; Purba, Kuras; Nababan, Dame Tiur Magdalena (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: The purpose of this dedication is so that every orphanage in Indonesia, especially in Medan City, can implement ISAK 335 in the preparation of its financial reports, so that large donors can trust the money they donate to the orphanage. Methodology/approach: The method used in this training is by means of an interview first, then conducting training in accounting records to financial reporting in accordance with the regulations in force in Indonesia. Results/findings: The result of this training was that the orphanage owners felt awkward because so far they did not know that there were financial reporting standards specifically for orphanages, because they only recorded their finances in the form of cash receipts and cash expenditures, and even then it was done on the notice board in the orphanage. Conclusions: The results of this service are that the two orphanages only record their finances in the form of cash in and cash out, without following the applicable standards. Limitations: The limitations of this service are in terms of time, where this service is only carried out for one day at each orphanage, the background of the orphanage owner is a high school graduate, so it takes a lot of time for training in order to be able to implement ISAK 335 in preparing financial reports and finally only 2 orphanages were trained. Contribution: This service is useful for orphanages so that they can prepare financial reports in accordance with existing regulations, so that donors have more confidence in the performance of orphanages.